Injectable tissue adhesive and application thereof
By using a composite material of hydrophilic polymer and block polymer, a high-strength, low-swelling tissue adhesive is formed, which solves the problems of easy swelling of the adhesive and poor mechanical properties in the prior art, and achieves physiological Long-term stable bonding and good mechanical properties in the environment are suitable for a variety of clinical and medical applications.
Patent Information
- Application Number
- CN202411609859.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-11
AI Technical Summary
Existing tissue adhesives are prone to swelling under physiological environments, have poor mechanical properties, and have toxicity and biodegradation problems, making it difficult to meet clinical needs.
A composite of hydrophilic polymer and block polymer is used to form a high-strength, low-swelling injectable tissue adhesive by covalently bonding through crosslinking groups. The adhesive consists of materials such as polyethylene glycol, poloxamer, and has adjustable mechanical properties and good cell/histocompatibility.
It achieves long-term stable adhesion under dynamic physiological environment, reduces swelling rate and improves mechanical properties, and avoids toxicity and biodegradation problems. It is suitable for applications such as trauma sealing, anti-adhesion and implanted device coatings.
Smart Images

Figure CN119405870A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of tissue adhesives, and specifically relates to an injectable tissue adhesive with low swelling rate and high bonding strength, specifically a tissue adhesive with good bonding, air permeability, adjustable mechanical strength and the ability to achieve long-term stable bonding under physiological conditions. Background Art
[0002] Commonly used tissue wound closure devices in clinical practice are sutures and fixation pins. There are some shortcomings that need to be solved during use: 1) The wound is prone to splitting when subjected to tension, and secondary tissue damage will be caused due to the mismatch of mechanical properties between the sutures and fixation pins and the tissue; 2) Due to the failure to completely seal, tissue fluid or gas in the wound is prone to leakage, which prolongs the wound healing time; 3) The use of sutures and fixation pins is time-consuming and requires professional medical staff to operate, making it difficult to deal with emergencies; 4) Sutures and fixation pins cannot be used for low-toughness tissues. Adhesives are increasingly attracting attention as a substitute for sutures and fixation pins or used together with sutures and fixation pins. Tissue adhesives can provide effective closure of the wound surface and prevent liquid leakage, becoming an important tool in surgery. In addition to being used in surgery, they are also widely used as wound dressings to quickly close skin wounds and provide an environment that promotes tissue regeneration. Adhesives achieve stable adhesion in the physiological environment, making them also useful for fixation between wearable / implantable devices and tissues and drug delivery.
[0003] Hydrogel materials are soft materials with high water content and three-dimensional network structure, and have similar physical and chemical properties to tissues. The special porous structure of hydrogel can promote the exchange of nutrients, absorb exudates, and maintain a moist environment for the wound, thereby accelerating the wound healing process (Q. Huang, Y. Zou, MC Arno, S. Chen, T. Wang, J. Gao, AP Dove and J. Du, Chem. Soc. Rev., 2017, 46, 6255-6275.). In addition, hydrogels also have many physical and chemical properties similar to extracellular matrix (ECM), which can promote cell proliferation, adhesion, migration and differentiation during wound healing (S. Tang, BM Richardson and KS Anseth, Prog. Mater. Sci., 2021, 120, 100738.). All of the above advantages make hydrogels the best candidates for preparing medical tissue adhesives. However, hydrogels are mostly composed of permanent covalent bonds or long-term stable strong physical bonds, and their mechanical characteristics are mainly elastic, so there are still many problems in tissue engineering applications. Under physiological conditions, adhesives are required to have low swelling properties. The traditional means of reducing swelling of hydrogels is mainly to increase the cross-linking density; but this method will reduce the pore size of the hydrogel network, which makes the mass transfer efficiency of cells inside the gel low and tends to apoptosis; and high cross-linking density will reduce the toughness of the hydrogel, limiting the use of adhesives in dynamic environments or large strain areas.
[0004] So far, a variety of adhesives have been developed for wound closure caused by trauma and surgery. However, the adhesives used in clinical practice still cannot meet clinical requirements due to the shortcomings of weak tissue adhesion, toxic components and uncontrollable biodegradation. For example, fibrin glue has been approved by the U.S. Food and Drug Administration (FDA) for closing and hemostasis of various types of wounds. However, its adhesion to tissues is weak (5-10 kPa) and there is a risk of blood-borne viral diseases (WD Spotnitz, World J. Surg. 2010, 34, 632-634.). Cyanoacrylate adhesives show higher bonding strength and have been approved for closing skin wounds; however, the potential toxicity of cyanoacrylate monomers and their degradation products easily leads to inflammatory reactions in surrounding tissues, limiting their internal clinical applications (AJSinger, JV Quinn, JE Hollander, Am. J. Emerg. Med. 2008, 26, 490-496.). Polyethylene glycol (PEG)-based tissue adhesives are a type of adhesive that has been widely used in the biomedical field in recent years, especially in wound repair, surgery, and tissue engineering. DuraSeal is a typical PEG-based hydrogel sealant. The components of the sealant form a cross-linked network through the amidation between the NHS ester group of 4-arm PEG-NHS and the amine group in trilysine. In addition, the sealant achieves covalent tissue adhesion by coupling the NHS ester group of 4aPEG-NHS with the amine group on the tissue surface. However, the main drawback of PEG-based adhesives, including DuraSeal, is that the hydrophilicity of PEG causes excessive swelling of the adhesive under physiological conditions, which is extremely harmful and even fatal when used in complex neural tissues such as the spine and the cranium. Therefore, it is of great significance to develop a tissue adhesive that has both biocompatibility, tissue adhesion, and low swelling. Summary of the invention
[0005] In order to solve the shortcomings of traditional hydrogels as tissue adhesives, the purpose of the present invention is to provide an injectable tissue adhesive with both low swelling rate and high bonding strength, and improve the problems of easy swelling and poor mechanical properties of the adhesive. The tissue adhesive of the present invention has a swelling rate of less than 50%, can stably exist for at least 3 days in a dynamic physiological environment, is non-toxic, has adjustable mechanical properties, and can quickly form stable adhesion with the surfaces of various materials including metals, plastics, glass, human tissues, etc.; a polymer material with good biocompatibility is used to obtain an adhesive hydrogel material with good cell / tissue compatibility, which can be used as a new type of suture-free wound dressing or as a coating for implanted devices.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The invention provides an injectable tissue adhesive with high strength and low swelling. The tissue adhesive is mainly composed of a hydrophilic polymer and a block polymer, the mass ratio of the hydrophilic polymer to the block polymer is 1:5 to 5:1; the hydrophilic polymer is selected from at least one of polyethylene glycol, polyvinyl alcohol, gelatin, hyaluronic acid, alginate and chitosan; the block polymer is poloxamer; the hydrophilic polymer is composed of hydrophilic polymers with two or more molecular weights, the poloxamer is composed of one or more types of poloxamer, the hydrophilic polymer and the block polymer are covalently connected via a cross-linking group, the hydrophilic polymer has good affinity with tissues and has a deeper penetration depth into the tissues, the block polymer with a hydrophobic segment can reduce swelling, and selecting a high molecular weight block polymer as an adhesive can provide more energy dissipation, and the bonding time of the tissues can be significantly prolonged by using the hydrophilic polymer and the block polymer in combination.
[0008] Based on the above technical solution, further, the volume percentage of the polymer in the tissue adhesive is 5%-80%, preferably 20%-60%.
[0009] Based on the above technical solution, further, the transmittance of the tissue adhesive is 60-100%, the viscosity of the pre-polymerized solution of the tissue adhesive is not higher than 10Pa.s, and the penetration depth in the tissue is not less than 20μm; the tissue bonding strength of the tissue adhesive after curing is 50-300kPa to ensure sufficient wound sealing effect and durability, and the volume swelling rate is less than 50%.
[0010] Based on the above technical solution, further, the mass ratio of the hydrophilic polymer to the block polymer is 1:2 to 2:1.
[0011] Based on the above technical solution, further, the polyethylene glycol is a straight-chain polyethylene glycol or a multi-branched polyethylene glycol, preferably a straight-chain polyethylene glycol.
[0012] Based on the above technical scheme, further, the molecular weight of the polyethylene glycol is 0.2kDa-6kDa, preferably 0.2kDa, 2kDa, 4kDa and 6kDa; the molecular weight of the polyvinyl alcohol is 2kDa-75kDa; the functional group modification degree of hyaluronic acid, chitosan and alginate is ≥50%; the functional group modification degree of gelatin is ≥60%.
[0013] Based on the above technical solution, further, the poloxamer is one or a combination of two or more of F127, F108, F88, F68, and F87, and has a molecular weight of 1 kDa-30 kDa.
[0014] Based on the above technical scheme, further, the mass ratio of 0.2kDa, 2kDa, 4kDa and 6kDa polyethylene glycol is 0-10:0-10:0-10:0-10; the mass ratio of F127, F108, F88, F68 and F87 is 0-10:0-10:0-10:0-10:0-10.
[0015] Based on the above technical scheme, further, the cross-linking group is obtained through free radical polymerization reaction or click chemistry reaction, the free radical polymerization group includes acrylate, methacrylate, allyl isocyanate, and the click chemistry reaction group includes azide / alkyne, thiol / double bond, diene / monoene, amino / aldehyde, furanyl / maleimide, succinimide / amino, epoxy / amino.
[0016] Based on the above technical solution, further, the preparation process of the injectable tissue adhesive is: dissolving a hydrophilic polymer modified with a cross-linking group on the end group and a block polymer modified with a cross-linking group on the end group in an aqueous solution to obtain a polymer aqueous solution with a concentration of 20-50% (w / v), and cross-linking is induced by light or chemical initiator;
[0017] Alternatively, one group of the click chemistry reaction group pair is covalently modified onto a hydrophilic polymer, and the click chemistry reaction groups on hydrophilic polymers of different molecular weights are the same and dissolved in an aqueous solution; the other group of the click chemistry reaction group pair is covalently modified onto a block polymer, and the click chemistry reaction groups on different types of block polymers are the same and dissolved in an aqueous solution; the obtained two solutions are uniformly mixed at a click chemistry reaction group pair molar ratio of 0.1 to 10 to obtain a polymer aqueous solution with a concentration of 20-50% (w / v), and cross-linking is performed through a click chemistry reaction.
[0018] Another aspect of the present invention provides a method for using the above-mentioned high-strength, low-swelling injectable tissue adhesive, the method comprising a first method and a second method;
[0019] Method 1: When the cross-linking group is selected from acrylate, methacrylate, and allyl isocyanate, the method comprises the following steps:
[0020] (1) dissolving a hydrophilic polymer having a cross-linking group modified at its terminal group and a block polymer having a cross-linking group modified at its terminal group in an aqueous solution to obtain a 1.5-100% (w / v) polymer aqueous solution;
[0021] (2) When the polymerization is initiated by light-induced crosslinking, a photoinitiator is added to a polymer aqueous solution and mixed evenly to obtain a prepolymer solution. The prepolymer solution is applied to the surface of the tissue to be bonded, and the prepolymer solution is irradiated with light to initiate a crosslinking reaction of the polymer and then solidify, thereby achieving stable adhesion of the tissue;
[0022] When the initiation polymerization method is chemical cross-linking, a chemical initiator is added to the polymer aqueous solution and mixed evenly to obtain a pre-polymer solution, and the pre-polymer solution is applied to the surface of the tissue to be bonded, and then the polymer in the polymer solution is allowed to cross-link and solidify for 10 seconds to achieve stable adhesion of the tissue;
[0023] Method 2: When the terminal modified group is selected from the group of click chemistry reaction groups such as azide / alkyne, thiol / double bond, amino / aldehyde, furanyl / maleimide, succinimide / amino, and epoxy / amino, the preparation steps are as follows:
[0024] 1) covalently modifying one of the click chemistry reaction groups to a hydrophilic polymer, wherein the click chemistry reaction groups on the hydrophilic polymers of different molecular weights are the same and dissolved in an aqueous solution;
[0025] 2) covalently modifying the other group of the click chemistry reaction group pair onto the block polymer, and the click chemistry reaction groups on different types of block polymers are the same and dissolved in an aqueous solution;
[0026] 3) The solution obtained in step 1) and the solution obtained in step 2) are mixed evenly according to a click chemistry reaction group molar ratio of 0.1 to 10, and after applying the mixed solution to the surface of the tissue to be bonded, wait for 10 seconds to 500 minutes to allow the click chemistry reaction in the polymer to fully proceed, so as to achieve stable adhesion with the tissue.
[0027] Based on the above technical solution, further, the concentration of the polymer aqueous solution in step (1) is 10-60% (w / v), preferably 20-50% (w / v).
[0028] Based on the above technical solution, further, the photoinitiator described in step (2) includes lithium phenyl-2,4,6-trimethylbenzoylphosphinate, and the light-induced wavelength range is 200-700nm.
[0029] Based on the above technical solution, further, the conditions for the photoinduced polymerization reaction in step (2) are that the photoinduced wavelength range is 360-405nm and the light intensity is 10-500mW / cm 2 , time 1-200s.
[0030] Based on the above technical solution, further, the chemical initiator described in step (2) includes ammonium persulfate / tetramethylethylenediamine.
[0031] Based on the above technical solution, further, the concentration of the polymer mixed solution in step 3) is 10-60% (w / v), preferably 20-50% (w / v).
[0032] Based on the above technical solution, further, the aqueous solution is a solution containing bioactive substances or biocompatible substances, and the bioactive substances are exosomes, vitamins, amino acids, mineral elements, microecological regulators, platelet-rich plasma (PRP), platelet-rich plasma fibrin (PRF), growth factors or blood. Biocompatible substances include starch, cellulose, chitosan, sodium alginate, hyaluronic acid, pullulan, xanthan gum, collagen, gelatin, fibrin and their derivatives, which refer to pure water or aqueous solutions containing biocompatible substances that do not affect the polymerization of adhesives into gels.
[0033] The present invention also provides the use of the above-mentioned high-strength, low-swelling injectable tissue adhesive as a wound sealing dressing. The adhesive is injected into the wound, and after polymerization and curing, it stably seals the wound surface and acts as a barrier to effectively protect the wound from water and bacterial infection, thereby accelerating the healing speed of the wound.
[0034] The present invention also provides the use of the above-mentioned high-strength, low-swelling injectable tissue adhesive as a postoperative anti-adhesion agent. The adhesive is injected into the postoperative adhesion prevention site, and after polymerization and curing, it stably covers the injured site and acts as a barrier to effectively prevent adhesion between postoperative tissues.
[0035] The present invention also provides the use of the above-mentioned high-strength, low-swelling injectable tissue adhesive as a coating product for implantable devices, wherein the adhesive is injected onto the surface of the implantable device, and the adhesive is attached to the surface of the implantable device through a polymerization reaction, thereby improving the biocompatibility of the implantable device or achieving adhesion between the implantable device and the tissue after the implantable device is bonded to the tissue.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] 1. The tissue adhesive of the present invention utilizes a unique combination of short-chain hydrophilic polymers of different molecular weights and different types of block copolymers. The introduction of short-chain hydrophilic polymers can effectively improve the mechanical strength of the adhesive and reduce the swelling rate; more importantly, the combination of hydrophilic polymers and block polymers can effectively shield the hydrophobic effect of the block polymers, increase its viscosity during application, and increase the permeability between the polymer and the tissue. At the same time, the unique combination of short-chain hydrophilic polymers of different molecular weights and different types of block copolymers significantly improves the elasticity and flexibility of the material, allowing it to adapt to the deformation of the tissue.
[0038] 2. The tissue adhesive of the present invention can effectively absorb external stress and reduce the stress acting on the adhesive part through energy dissipation. Compared with traditional single hydrogel adhesives, the tissue adhesive prepared by the present invention can have a longer adhesion time with tissues in a dynamic environment, and also effectively prevent bacteria and moisture from the external environment from entering the interior, thereby improving the adhesion time of the adhesive.
[0039] 3. The present invention uses different ratios of hydrophilic and hydrophobic polymers to achieve regulation of the mechanical properties of the adhesive, while also regulating the swelling properties of the adhesive to meet different application requirements.
[0040] 4. The adhesive of the present invention has good cell compatibility and can promote the repair of mouse skin injuries as a wound closure dressing. Compared with the commercial tissue glue in the control group, the healing effect is more significant.
[0041] 5. Experimental results show that the adhesive of the present invention can effectively prevent tissue adhesion in the postoperative area in vivo.
[0042] 6. The tissue adhesive of the present invention has excellent adhesive properties and can be used in the biomedical field as a wound closure dressing, a tissue anti-adhesion material, and an implant device coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the embodiments of the present invention, the drawings related to the embodiments are briefly introduced below.
[0044] Figure 1 Flow chart of injecting the hydrogel tissue adhesive into the wound site in Example 1.
[0045] Figure 2 Schematic diagram of the customized burst pressure test device of Example 1.
[0046] Figure 3 This is a diagram showing the effect of the hydrogel tissue adhesive of Example 1 on the adhesion between different tissues.
[0047] Figure 4 4 is a graph showing the hemolysis rate of the blood compatibility of the tissue adhesive of Example 1.
[0048] Figure 5 : is the cell compatibility graph of the tissue adhesive of Example 1.
[0049] Figure 6 These are optical images of the tissue adhesive of Example 1 and Comparative Example 17 after liver hemostasis was completed.
[0050] Figure 7 The HE staining pictures of the tissue sections of the tissue adhesive of Example 1 and Comparative Example 17 7 days or 14 days after liver hemostasis.
[0051] Figure 8 It is a diagram showing the process of cardiac hemostasis by the tissue adhesive of Example 1 and a HE section staining diagram of the tissue after hemostasis by the tissue adhesive.
[0052] Fig. 9 This is a diagram showing the process of hemostasis of the tissue adhesive of Example 1 in a pig femoral artery.
[0053] Fig.10 This is an optical image of the tissue adhesive of Example 1 healing on the dura mater.
[0054] Fig.11 The optical images are of the tissue adhesive of Example 1 and Comparative Example 19 for anti-adhesion filling on liver wound surface.
[0055] Fig.12 This is a photograph of the tissue adhesive of Example 1 after filling the back of a rat as a subcutaneous filling material.
[0056] Fig.13 is an optical image of the tissue adhesive of Example 2 applied as a hydrogel coating on a PDMS surface. DETAILED DESCRIPTION
[0057] Various embodiments and specific implementations will be described in detail below. These embodiments should not be construed as limiting the scope of this patent application in any way, and changes and modifications may be made without departing from the essence and scope of the present invention. In addition, only some end uses are discussed herein, but end uses not specifically described herein are also included in the scope of this application. Therefore, the scope of this patent application should be determined by the claims.
[0058] The present invention solves the problem of complicated wound sealing operation and the inadequacy of existing adhesive performance, and proposes a new tissue adhesive formula to improve the problem of easy swelling and poor mechanical properties of the adhesive. The adhesive has a polymer with terminal group modification, and the adhesive penetrates and diffuses on the multi-layer carrier and tissue surface and polymerizes in situ to form mechanical interlocking and physical entanglement to achieve adhesion. The different proportions of hydrophilic and block polymers in the adhesive make the adhesive have adjustable bonding strength and swelling rate, which can match different tissue surfaces. At the same time, the liquid adhesive can also adapt to different wound shapes.
[0059] The adhesive part of the tissue adhesive of the present invention may include any adhesive with in-situ polymerizable properties. The adhesive is formed by mixing a hydrophilic polymer and a block polymer. In some embodiments, the hydrophilic polymer in the adhesive accounts for 1-30% of the total mass fraction, and the hydrophobic polymer accounts for 5-30% of the total mass fraction.
[0060] The present application will be further described below with reference to examples and comparative examples.
[0061] The molecular weight of F127 used in the examples is 12.6 kDa, the molecular weight of F108 is 14.6 kDa, the molecular weight of F88 is 11.4 kDa, the molecular weight of F68 is 8.4 kDa, and the molecular weight of F87 is 7.7 kDa.
[0062] Examples 1-8
[0063] Synthesis of hydrophilic cross-linked polymer: 50g of polyethylene glycol (PEG, Table 1) of different molecular weights was dissolved in 150mL of anhydrous dichloromethane, and 10mL of triethylamine and 9mL of acryloyl chloride were added in turn to react at room temperature for 24 hours. After the reaction, the impurities were washed with an aqueous solution of magnesium carbonate, extracted and separated, and the obtained organic phase was precipitated in ether, and the precipitate was freeze-dried to obtain PEGDA. PEG of different molecular weights can be selected to prepare PEGDA of corresponding molecular weight according to the above method.
[0064] Synthesis of hydrophobic cross-linked polymer: 50g of different types of block polymers Pluronic (Table 1) were dissolved in 150mL of anhydrous dichloromethane, and 8mL of triethylamine and 7mL of acryloyl chloride were added in turn to react at room temperature for 24 hours. After the reaction, the impurities were washed with an aqueous solution of magnesium carbonate, extracted and separated, and the obtained organic phase was precipitated in ether, and the precipitate was freeze-dried to obtain Pluronic grafted with acrylate groups. Pluronics of different molecular weights and different types can be selected and prepared according to the above method.
[0065] A total mass of 40 g of hydrophilic cross-linked polymer and hydrophobic polymer (the masses of hydrophilic polymers with different molecular weights and different types of hydrophobic polymers are shown in Table 1) were mixed in 100 mL of aqueous solution and stirred at 25 °C for 1 h to obtain a uniform mixed solution. 0.05 g of phenyl-2,4,6-trimethylbenzoyl lithium phosphinate was added to the mixed solution and mixed evenly. Then 1 mL was injected into a silicone mold and heated at 365 nm, 50 mW / cm 2 After irradiating under blue ultraviolet light for 10 seconds, the sample was taken out to obtain a hydrogel.
[0066] The hydrogels prepared in Examples 1-8 were immersed in a PBS buffer solution at 37° C. The volume change of the hydrogels was calculated at a specific time to determine the volume swelling rate thereof. The specific data are shown in Table 2.
[0067] 0.05 g of phenyl-2,4,6-trimethylbenzoylphosphinate lithium was added to the adhesive prepolymer solution obtained in Example 1-8 and mixed evenly. Then 200 μL was injected on the surface of pig skin and the PET backing was covered with 10 mm 2 The area was overlapped on the pig skin and 365nm, 50mW / cm 2After irradiation under ultraviolet light for 10 seconds, the sample was placed on a mechanical testing machine and loaded to failure at a speed of 5 mm / min. The load at failure was recorded and the test overlap was calculated. The specific data are shown in Table 3.
[0068] Fresh pig skin was fixed on the upper surface of a custom-made burst pressure device (device as Figure 2 A circular hole with a diameter of 2 mm was created in the center of the pig skin in the device. Thereafter, 500 μL of the prepolymerized solution of Examples 1-8 was injected at the puncture site and illuminated. The measuring device was connected to a syringe pump filled with PBS solution. Finally, the PBS solution was injected into the device, and the maximum burst pressure was recorded using a digital pressure gauge (MIK-Y180, Asmik, China), and the specific data are shown in Table 3.
[0069] 0.05 g of phenyl-2,4,6-trimethylbenzoylphosphinate lithium was added to the mixed solution obtained in Example 1-8 and mixed evenly. Then 200 μL was injected onto the surface of pig skin and the PET backing was covered with 10 mm 2 The area was overlapped on the pig skin and 365nm, 50mW / cm 2 After irradiation with ultraviolet light for 10 seconds, the samples were immersed in PBS at 37°C for 3 days to observe whether the tissue fell off to determine the long-term adhesion stability. The specific data are shown in Table 3.
[0070] Table 1 Mass of hydrophilic polymers and hydrophobic polymers
[0071]
[0072] Table 2 Swelling rate of hydrogels prepared in Examples 1-8 in PBS buffer
[0073]
[0074] Table 3 Lap bonding strength, burst pressure and whether it falls off after immersion of the prepolymerized solution of Examples 1-8
[0075] Overlap bond strength Burst Pressure Whether it falls off Example 1 203kPa 132kPa no Example 2 187kPa 113kPa no Example 3 168kPa 93kPa no Example 4 193kPa 106kPa no Example 5 183kPa 97kPa no Example 6 178kPa 89kPa no Example 7 195kPa 118kPa no Example 8 188kPa 93kPa no
[0076] Comparative Examples 1-8
[0077] Synthesis of hydrophilic cross-linked polymer: 50g of polyethylene glycol (PEG, Table 4) of different molecular weights was dissolved in 150mL of anhydrous dichloromethane, and 10mL of triethylamine and 9mL of acryloyl chloride were added in turn to react at room temperature for 24 hours. After the reaction, the impurities were washed with an aqueous solution of magnesium carbonate, extracted and separated, and the obtained organic phase was precipitated in ether, and the precipitate was freeze-dried to obtain PEGDA. PEG of different molecular weights can be selected to prepare PEGDA of corresponding molecular weight according to the above method.
[0078] Synthesis of hydrophobic cross-linked polymer: 50 g of different types of block polymers Pluronic (Table 1) were dissolved in 150 mL of anhydrous dichloromethane, and 8 mL of triethylamine and 7 mL of acryloyl chloride were added in turn to react at room temperature for 24 hours. After the reaction, the impurities were washed with an aqueous solution of magnesium carbonate, extracted and separated, and the obtained organic phase was precipitated in ether, and the precipitate was freeze-dried to obtain Pluronic grafted with acrylate groups.
[0079] 20 g or 40 g of hydrophilic polymer or hydrophobic polymer were mixed in 100 mL of aqueous solution. The specific parameters were shown in Table 4. 0.05 g of phenyl-2,4,6-trimethylbenzoylphosphinate lithium was added to the mixed solution and mixed evenly. Then 1 mL was injected into a silicone mold and heated at 365 nm, 50 mW / cm 2 The hydrogels prepared in Comparative Examples 1-8 were immersed in a PBS buffer solution at 37°C, and the volume change of the hydrogels was calculated at a specific time to determine the volume swelling rate. The specific data are shown in Table 5.
[0080] 0.05 g of phenyl-2,4,6-trimethylbenzoyl lithium phosphinate was added to the hydrogel prepolymer obtained in Comparative Example 1-8 and mixed evenly. The overlapping bonding strength, bursting pressure and whether the adhesive fell off after immersion in PBS solution at 37° C. for 3 days were tested with reference to the method in Example 1-8. The results are shown in Table 6.
[0081] Table 4 Mass of hydrophilic polymers and hydrophobic polymers
[0082]
[0083] Table 5 Swelling rate of hydrogels prepared in Comparative Examples 1-8 in PBS buffer
[0084]
[0085] Table 6 Results of lap bonding strength, burst pressure and whether the prepolymer solution of Comparative Examples 1-8 falls off after immersion
[0086] Overlap bond strength Burst Pressure Whether it falls off Comparative Example 1 33kPa 21kPa yes Comparative Example 2 47kPa 20kPa yes Comparative Example 3 32kPa 15kPa yes Comparative Example 4 28kPa 13kPa yes Comparative Example 5 25kPa 14kPa yes Comparative Example 6 32kPa 14kPa yes Comparative Example 7 26kPa 16kPa yes Comparative Example 8 23kPa 11kPa yes
[0087] Examples 9-16 (Chemical Crosslinking)
[0088] The synthesis of hydrophilic cross-linked polymer and hydrophobic cross-linked polymer is the same as that of Example 1-8.
[0089] A total mass of 40 g of hydrophilic polymer and hydrophobic polymer (the mass of hydrophilic polymers with different molecular weights and different types of hydrophobic polymers is shown in Table 7) was mixed together in 100 mL of aqueous solution and stirred at 25 ° C for 1 h to obtain a uniform hydrogel solution. The specific parameters are shown in Table 7. Take 1 mL of the prepolymer solution and then add 5 mg of ammonium persulfate and tetramethylethylenediamine solution respectively, mix quickly and evenly, and then inject into the silicone mold. Wait for 10 minutes and take it out to obtain a hydrogel.
[0090] The hydrogels prepared in Examples 9-16 were immersed in a PBS buffer solution at 37° C. The volume change of the hydrogels was calculated at a specific time to determine their volume swelling rate. The specific data are shown in Table 8.
[0091] Take 200 μL of the bonding prepolymer solution obtained in Examples 9-16 and add 1 mg of ammonium persulfate and tetramethylethylenediamine solution. Refer to the method in Examples 1-8 to test the lap bonding strength, bursting pressure and whether the adhesive falls off after immersion in PBS solution at 37°C for 3 days. The results are shown in Table 9.
[0092] Table 7 Mass of hydrophilic polymers and hydrophobic polymers
[0093]
[0094] Table 8 Swelling rate of hydrogels prepared in Examples 9-16 in PBS buffer
[0095]
[0096] Table 9 Lap bonding strength, burst pressure and whether it falls off after immersion of the prepolymer solution of Examples 9-16
[0097] Overlap bond strength Burst Pressure Whether it falls off Example 9 201kPa 128kPa no Example 10 188kPa 115kPa no Embodiment 11 156kPa 100kPa no Example 12 183kPa 112kPa no Embodiment 13 168kPa 102kPa no Embodiment 14 168kPa 83kPa no Embodiment 15 187kPa 108kPa no Example 16 168kPa 76kPa no
[0098] Comparative Examples 9-16
[0099] The synthesis of hydrophilic cross-linked polymer and hydrophobic cross-linked polymer is the same as that of Example 1-8.
[0100] 40 g of hydrophilic polymer and hydrophobic polymer were mixed in 100 mL of aqueous solution and stirred at 25 °C for 1 h to obtain a uniform hydrogel solution. The specific parameters are shown in Table 10. 1 mL of prepolymer solution was taken and then 5 mg of ammonium persulfate and tetramethylethylenediamine solution were added respectively. After rapid mixing, the mixture was injected into a silicone mold. After waiting for 10 minutes, the mixture was taken out to obtain a hydrogel.
[0101] The hydrogels prepared in Comparative Examples 9-16 were immersed in a PBS buffer solution at 37° C. The volume change of the hydrogels was calculated at a specific time to determine their volume swelling rate. The specific data are shown in Table 11.
[0102] Take 200 μL of the bonding prepolymer solution obtained in Comparative Examples 9-16 and add 1 mg of ammonium persulfate and tetramethylethylenediamine solution. Refer to the method in Example 1-8 to test the lap bonding strength, bursting pressure and whether the adhesive falls off after immersion in PBS solution at 37°C for 3 days. The results are shown in Table 12.
[0103] Table 10 Mass of hydrophilic polymers and hydrophobic polymers
[0104]
[0105] Table 11 Swelling rate of hydrogels prepared in comparative examples 9-16 in PBS buffer
[0106]
[0107] Table 12 Results of lap bonding strength, bursting pressure and whether the prepolymerized solutions of comparative examples 9-16 fall off after immersion
[0108] Overlap bond strength Burst Pressure Whether it falls off Comparative Example 9 36kPa 21kPa yes Comparative Example 10 43kPa 18kPa yes Comparative Example 11 34kPa 20kPa yes Comparative Example 12 26kPa 14kPa yes Comparative Example 13 28kPa 17kPa yes Comparative Example 14 30kPa 18kPa yes Comparative Example 15 34kPa 16kPa yes Comparative Example 16 27kPa 14kPa yes
[0109] Examples 17-22 (different groups grafted, different groups selected)
[0110] The molecular weight and ratio of hydrophilic and hydrophobic polymers in Example 1 are used as reference. Take 10 grams of 0.6 kDa and 4 kDa PEG containing click chemical groups (the click chemical groups of 0.6 kDa and 4 kDa PEG are the same, which are sulfhydryl, azide, amino, succinimide, grafted on the hydroxyl groups in PEG, see Table 13), and 10 grams of F127 and F108 containing click chemical groups (the click chemical groups of F127 and F108 are the same, which are olefins, alkynes, aldehydes, and amino groups, grafted on the hydroxyl groups of F127 and F108, see Table 13), a total of 40 g, wherein the polymers with the same end groups are dissolved in the same 50 mL aqueous solution, and the specific parameters are as described in Table 13. Stir at 25 ° C for 1 hour to obtain a uniform solution. Take a specific volume and molar ratio of solutions containing different groups, mix them quickly and evenly, and then inject them into a silicone mold. Wait for 10 minutes and take it out to obtain a hydrogel.
[0111] The hydrogels prepared in Examples 17-22 were immersed in a PBS buffer solution at 37° C. The volume change of the hydrogels was calculated at a specific time to determine their volume swelling rate. The specific data are shown in Table 14.
[0112] The prepolymer solutions obtained in Examples 17-22 were tested for lap bonding strength, bursting pressure, and whether the adhesive fell off after being immersed in PBS solution at 37°C for 3 days using the methods described in Examples 1-8. The results are shown in Table 15.
[0113] Table 13 Cross-linking groups and ratios of hydrophilic and hydrophobic polymers
[0114] Cross-linking group Crosslinking group molar ratio Embodiment 17 Mercapto / Olefin 1:1 Embodiment 18 Azide / Alkyne 1:1 Embodiment 19 Amino / aldehyde 1:1 Embodiment 20 Succinimidyl / amino 1;1 Embodiment 21 Succinimidyl / amino 10:1 Embodiment 22 Succinimidyl / amino 1:10
[0115] Table 14 Swelling rate of hydrogel in PBS buffer
[0116]
[0117] Table 15 Results of lap bonding strength, bursting pressure and whether it falls off after immersion of prepolymer solution
[0118] Overlap bond strength Burst Pressure Whether it falls off Embodiment 17 122kPa 96kPa no Embodiment 18 124kPa 95kPa no Embodiment 19 123kPa 95kPa no Embodiment 20 121kPa 103kPa no Embodiment 21 129kPa 104kPa no Embodiment 22 123kPa 105kPa no
[0119] Examples 23-30 (blending of different aqueous solutions)
[0120] According to Example 1, the hydrophilic and hydrophobic polymers were mixed together in 100 mL of aqueous solution, and the aqueous solutions were vitamin C (10 mg / mL), glycine (30 mg / mL), platelet-rich plasma fibrin, blood, starch solution (10 mg / mL), hyaluronic acid solution (10 mg / mL), gelatin solution (10 mg / mL), and methacrylic acid modified gelatin (GelMA) solution (10 mg / mL). Stir at 25°C for 1 hour to obtain a uniform solution. The specific parameters are as described in Table 16. 0.05 g of phenyl-2,4,6-trimethylbenzoyl lithium phosphinate was added to the mixed solution and mixed evenly. Then 1 mL was injected into a silicone mold and the mixture was heated at 365 nm, 50 mW / cm 2 After irradiating under blue ultraviolet light for 10 seconds, the sample was taken out to obtain a hydrogel.
[0121] The hydrogels prepared in Examples 23-30 were immersed in a PBS buffer solution at 37° C. The volume change of the hydrogels was calculated at a specific time to determine their volume swelling rate. The specific data are shown in Table 17.
[0122] Add 0.05 g of phenyl-2,4,6-trimethylbenzoyl lithium phosphinate to the adhesive prepolymer solution obtained in Examples 23-30 and mix well. Refer to the method in Examples 1-8 to test the lap bonding strength, bursting pressure and whether the adhesive falls off after immersion in PBS solution at 37°C for 3 days. The results are shown in Table 16.
[0123] Table 16 Results of lap bonding strength, bursting pressure and whether it falls off after immersion of prepolymer solution
[0124]
[0125] Table 17 Swelling rate of hydrogel in PBS buffer
[0126]
[0127] Example 31 (Tissue Penetration of Prepolymerized Solution)
[0128] Fluorescent groups were grafted onto the surfaces of hydrophilic and hydrophobic polymers to observe the penetration ability of the prepolymer solution on the tissue surface. The specific fluorescent grafting steps were as follows: 10 g of polyethylene glycol and pluronic were dissolved in 50 mL of dichloromethane respectively, 20 mL of triethylamine was added, and 1 g of p-toluenesulfonyl chloride in 10 mL of dichloromethane solution was added dropwise under stirring. The addition was completed within 30 minutes. After stirring overnight, the mixture was washed with 1 mol / L hydrochloric acid solution, washed three times with water and saturated sodium bicarbonate solution, dried with anhydrous magnesium sulfate, and then rotary evaporated. Hexane was added for precipitation. After the product was dried, 1 g was weighed and dissolved in 10 mL of water. 10 mg of rhodamine-isothiocyanate was added and stirred for 5 hours. After extraction with dichloromethane solution, the organic phase was taken and dried with anhydrous magnesium sulfate. After rotary evaporation, it was precipitated with hexane.
[0129] The polymer grafted with fluorescence was dissolved in the proportions in Example 1-8 to prepare a prepolymer solution, 10 μL was added dropwise to the surface of pig liver and skin tissue, and a confocal scanning microscope was used to excite the sample at 595 nm to measure the fluorescence depth. The results are shown in Table 18.
[0130] Table 18 Tissue penetration results of prepolymer solutions prepared in Examples 1-8
[0131] Example 1 2 3 4 5 6 7 8 liver 130 132 123 122 117 109 112 118 skin 115 193 141 93 83 105 129 141
[0132] Comparative Example 17 (Tissue Penetration of Prepolymerized Solution)
[0133] Fluorescent groups were grafted onto the surfaces of hydrophilic and hydrophobic polymers to observe the penetration ability of the adhesive. The specific fluorescent grafting steps were as follows: 10 grams of polyethylene glycol and pluronic were dissolved in 50 mL of dichloromethane respectively, 20 mL of triethylamine was added, and 1 gram of p-toluenesulfonyl chloride in 10 mL of dichloromethane solution was added dropwise under stirring. The addition was completed in 30 minutes. After stirring overnight, the mixture was washed with 1 mol / L hydrochloric acid solution, washed three times with water and saturated sodium bicarbonate solution, dried with anhydrous magnesium sulfate, and then precipitated with n-hexane. After the product was dried, 1 gram was weighed and dissolved in 10 mL of water, 10 mg of rhodamine-isothiocyanate was added and stirred for 5 hours, and then extracted with dichloromethane solution. The organic phase was taken and dried with anhydrous magnesium sulfate, and precipitated with n-hexane after rotary evaporation.
[0134] The polymer grafted with fluorescence was dissolved according to the proportions in Comparative Examples 1-8 to prepare a prepolymer solution, 10 μL of which was dropped onto the surface of pig liver and skin tissue, and a confocal scanning microscope was used to excite the sample at 595 nm and measure the fluorescence depth. The results are shown in Table 19.
[0135] Table 19 Tissue penetration results of prepolymer solutions prepared in Comparative Examples 1-8
[0136] Comparative Example 1 2 3 4 5 6 7 8 liver 16 13 10 14 8 4 15 12 skin 7 8 10 3 6 8 9 11
[0137] Example 32 (Adhesion of different tissues)
[0138] The binder prepolymer solution prepared in Example 1 was used, 0.05 g of phenyl-2,4,6-trimethylbenzoyl lithium phosphinate was added and mixed evenly, 200 μL of the mixed solution was injected on the surface of different ex vivo tissues (heart, liver, lung, kidney, stomach), and covered with a glass sheet. The surface was illuminated with 365 nm, 50 mW / cm 2 After 10s of UV exposure.
[0139] The results are as follows Figure 3 As shown, according to Figure 3 It can be observed that different in vitro tissues can be well adhered to the surface of the glass slide.
[0140] Example 33 (Hemolysis Experiment)
[0141] 5 mL of blood was collected from rabbit ears and stored at 4°C. Then 1 mL of anticoagulated blood was added to 2 mL of normal saline, and the diluted blood was shaken; 0.2 g of the hydrogel adhesive prepared in Example 1 was placed in a centrifuge tube, and 2 mL of normal saline was added, wherein the negative control group was blank and 1 mL of normal saline was added, and the positive control group was blank and 1 mL of distilled water was added, and 1 mL of the sample solution was taken from the experimental group, and 3 parallel tubes were used. Incubate in a constant temperature water bath (37°C) for 30 minutes, and 0.2 mL of diluted blood was added to all tubes except the blank tube, and shaken; culture at a constant temperature for 60 minutes; after shaking, centrifuge at 800g for 5 minutes, take the supernatant and add it to a 96-well plate, and measure the absorbance at 545 nm using an enzyme reader. The hemolysis rate of distilled water was set to 100%, and the hemolysis rate of normal saline was set to 0%. Calculate the hemolysis rate of the hydrogel material.
[0142] Results Figure 4 , Figure 4 The results confirmed that the adhesive had good blood compatibility.
[0143] Example 34 (Cytocompatibility)
[0144] The biocompatibility of the adhesive prepared in the proportion of Example 1 was investigated by in vitro cell culture experiments. The specific implementation steps are as follows:
[0145] The adhesive was irradiated with ultraviolet light (wavelength: 365 nm, intensity: 50 mW / cm 2 ) was irradiated for 30 seconds to obtain a hydrogel, and the gel was immersed in a culture medium (concentration 0.2 g / mL) and extracted for 24 hours for use; L929 cells (mouse fibroblast cell line, ATCC cell bank) were digested with trypsin and cultured overnight in a 24-well plate at 37°C and 5% carbon dioxide concentration to allow the cells to adhere to the well plate, and then the culture medium was aspirated and replaced with an extract, and then cultured at 37°C and 5% carbon dioxide concentration for 24 hours, and the cells in the gel extract were stained with a fluorescent live / dead assay to evaluate the viability of the hydrogel-encapsulated cells, wherein green fluorescence represents live cells and red fluorescence represents dead cells.
[0146] The results are as follows Figure 5 As shown, according to Figure 5 The results show that the adhesive prepared in Example 1 has good biocompatibility.
[0147] Example 35 (rat liver hemostasis)
[0148] The adhesive prepared in Example 1 was used to form a rat liver tissue defect model and linearly cut (length: 15 mm). 200 μL of the adhesive was dropped on the wound surface of the mouse liver tissue and ultraviolet light (wavelength: 365 nm, intensity: 50 mW / cm 2 ) After irradiation, the wound site was glued. On the 7th and 14th days after surgery, the wound healing site was photographed to record the wound healing status of each group, and liver tissue was sampled and HE sectioned and stained.
[0149] HE staining was performed on the tissues at 7 and 14 days after surgery. Figure 7 HE staining showed that the liver tissue defect sealed by the adhesive was completely healed within 7 days, and the healing effect was significantly better than that of cyanoacrylate (CA).
[0150] Comparative Example 18
[0151] Commercial tissue glue (cyanoacrylate (CA)) (0.1 mL) was used as the control group. The specific operation process was the same as that of Example 36, and the wound healing sites of rat livers were photographed to record the wound healing conditions of each group.
[0152] The results are as follows Figure 7 As shown, by comparison, it can be seen that the treatment effect of the liver wound treated with the adhesive prepared in Example 1 was significantly improved, and the wound gradually recovered within 7 days after treatment. In contrast, the liver of the commercial tissue glue showed only partial healing.
[0153] Example 36 (Heart Hemostasis)
[0154] The adhesive prepared in Example 1 was used to puncture the rat heart using a rat heart puncture model. A 10 mL syringe needle was used to puncture the rat heart. 200 μL of the adhesive was dropped on the wound surface of the mouse heart and ultraviolet light (wavelength: 365 nm, intensity: 50 mW / cm 2 ) After irradiation, the wound site was bonded. Seven days after the operation, the heart samples were taken out, and the wound healing sites were photographed to record the wound healing status of each group. The tissue was also stained with HE. The staining results showed that the adhesive could stably bond to the surface of the heart tissue ( Figure 8 ).
[0155] Example 37 (Femoral Artery Hemostasis)
[0156] The adhesive prepared in Example 1 was used to puncture the femoral artery of a pig using a puncture needle to create a 6*2 mm puncture wound. 500 μL of the adhesive was dropped onto the wound surface of the pig femoral artery and ultraviolet light (wavelength: 365 nm, intensity: 50 mW / cm 2 ) After irradiation, the wound site was glued. After stopping the hemostasis operation, observe whether there is still blood oozing out of the femoral artery bleeding point.
[0157] The results are as follows Fig. 9 As shown, complete hemostasis was achieved in the porcine femoral artery after adhesive closure, demonstrating that adhesive can be used for effective hemostasis of arteries.
[0158] Example 38 (Dura mater closure)
[0159] The adhesive prepared in Example 1 was used to drill holes in the rat dura mater damage model using a 5 mm bone drill at the predetermined location of the rat skull parietal bone. After exposing the dura mater, the dura mater was destroyed using microscissors. After cerebrospinal fluid exudation was observed, it was cleaned with gauze, and 20 μL of the adhesive was dropped on the dura mater damage site and ultraviolet light (wavelength: 365 nm, intensity: 50 mW / cm 2 ) After irradiation, the wound site was bonded. The wound healing site was photographed to record the wound healing status of each group.
[0160] The results are as follows Fig.10 As shown, according to Fig.10 The experiment showed that the adhesive prepared in Example 1 can heal the lesions at the dura mater within 7 to 28 days.
[0161] Example 39 (Anti-adhesion)
[0162] The adhesive prepared in Example 1 was used to form a rat liver tissue defect model and linearly cut (length: 15 mm). 200 μL of the adhesive was dropped on the wound surface of the mouse liver tissue and ultraviolet light (wavelength: 365 nm, intensity: 50 mW / cm 2) After irradiation, the wound site was bonded. The wound healing site was photographed to record the wound healing status of each group.
[0163] The results are as follows Fig.11 As shown, it can be observed that the adhesive in Example 1 can prevent other tissues from adhering to the surface of liver tissue within 7 days.
[0164] Comparative Example 19
[0165] Commercial CA glue was used as the control group, and a rat liver tissue defect model was used, and linear cutting (length: 15 mm) was performed, and CA glue was dropped on the wound surface of the mouse liver tissue to bond the wound site. The wound healing site was photographed to record the wound healing status of each group.
[0166] The results are as follows Fig.11 As shown, in contrast, wounds treated with commercial CA also showed wound healing, but with severe tissue adhesion and partial healed liver.
[0167] Example 40 (Subcutaneous filling)
[0168] Using the hydrogel material in Example 1, 50 μL of the hydrogel adhesive was cured in vitro for later use. A 10 mm incision was made on the back of the rat with a scalpel, and the subcutaneous tissue was separated using forceps to form a subcutaneous pouch. After the prepared hydrogel material was placed therein, the skin was sutured, and the mice were killed at 1 / 4 / 8 / 12 weeks, and the subcutaneous tissue containing the implanted material was removed, and the tissue samples were fixed in a fixative. Hematoxylin-eosin staining was used to observe whether tissue inflammation was caused and whether the material was still present in the subcutaneous tissue.
[0169] The results are as follows Fig.12 As shown, the hydrogel prepared in Example 1 can be stably filled into the subcutaneous tissue of the rat's back to maintain complete filling, and after 4 months, stable filling can still be achieved.
[0170] Example 41 (Hydrogel Coating)
[0171] Use deionized water and ethanol to clean the substrate to be coated (such as glass, metal or plastic) to remove impurities such as oil and dust on the surface. And the surface of the substrate is plasma treated or acidic to enhance its hydrophilicity. Spin or scrape 1mL of the hydrogel prepolymer solution prepared in Example 2 onto the surface of the substrate. The coated substrate is cross-linked with ultraviolet light for 1min to promote the cross-linking reaction of the hydrogel to form a stable hydrogel network structure, and an optical image of the formed hydrogel coating is obtained.
[0172] The results are as follows Fig.13 As shown, the results indicate that the hydrogel prepared in Example 2 can stably adhere to the polymer surface and be used as a hydrogel coating.
[0173] For any technician familiar with the field, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A high-strength, low-swelling injectable tissue adhesive, characterized in that: The tissue adhesive is mainly composed of a hydrophilic polymer and a block polymer, the mass ratio of the hydrophilic polymer to the block polymer is 1:5 to 5:1; the hydrophilic polymer is selected from at least one of polyethylene glycol, polyvinyl alcohol, gelatin, hyaluronic acid, alginate, and chitosan; the block polymer is poloxamer; the hydrophilic polymer is composed of hydrophilic polymers of two or more molecular weights, the poloxamer is composed of one or more types of poloxamer, and the hydrophilic polymer and the block polymer are covalently connected via a cross-linking group.
2. The injectable tissue adhesive according to claim 1, characterized in that: The volume percentage of the polymer in the tissue adhesive is 5%-80%, preferably 20%-60%; the transmittance of the tissue adhesive is 60-100%, the viscosity of the prepolymer solution of the tissue adhesive is not higher than 10Pa.s, and the penetration depth in the tissue is not lower than 20μm; the tissue bonding strength of the tissue adhesive after curing is 50-300kPa, and the volume swelling rate is lower than 50%.
3. The injectable tissue adhesive according to claim 1, characterized in that: The mass ratio of the hydrophilic polymer to the block polymer is 1:2 to 2:1; the polyethylene glycol is a linear polyethylene glycol or a multi-branched polyethylene glycol, preferably a linear polyethylene glycol; the molecular weight of the polyethylene glycol is 0.2kDa-6kDa, preferably 0.2kDa, 2kDa, 4kDa and 6kDa; the molecular weight of polyvinyl alcohol is 2kDa-75kDa; the functional group modification degree of hyaluronic acid, chitosan and alginate is ≥50%; the functional group modification degree of gelatin is ≥60%; the poloxamer is one or a combination of two or more of F127, F108, F88, F68 and F87, and the molecular weight is 1kDa-30kDa.
4. The injectable tissue adhesive according to claim 1, characterized in that: The cross-linking groups are obtained through free radical polymerization or click chemistry reaction. The free radical polymerization groups include acrylate, methacrylate, and allyl isocyanate. The click chemistry reaction groups include azide / alkyne, thiol / double bond, diene / monoene, amino / aldehyde, furanyl / maleimide, succinimide / amino, and epoxy / amino.
5. The method for using the high-strength, low-swelling injectable tissue adhesive according to any one of claims 1 to 4, characterized in that: The method of use includes method one and method two; Method 1: When the cross-linking group is selected from acrylate, methacrylate, and allyl isocyanate, the method comprises the following steps: (1) dissolving a hydrophilic polymer having a cross-linking group modified at its terminal group and a block polymer having a cross-linking group modified at its terminal group in an aqueous solution to obtain a 1.5-100% (w / v) polymer aqueous solution; (2) When the polymerization is initiated by light-induced crosslinking, a photoinitiator is added to a polymer aqueous solution and mixed evenly to obtain a prepolymer solution. The prepolymer solution is applied to the surface of the tissue to be bonded, and the prepolymer solution is irradiated with light to initiate a crosslinking reaction of the polymer and then solidify, thereby achieving stable adhesion of the tissue; When the initiation polymerization method is chemical cross-linking, a chemical initiator is added to the polymer aqueous solution and mixed evenly to obtain a pre-polymer solution, and the pre-polymer solution is applied to the surface of the tissue to be bonded, and then the polymer in the polymer solution is allowed to cross-link and solidify for 10 seconds to achieve stable adhesion of the tissue; Method 2: When the terminal modified group is selected from the group of click chemistry reaction groups such as azide / alkyne, thiol / double bond, amino / aldehyde, furanyl / maleimide, succinimide / amino, and epoxy / amino, the preparation steps are as follows: 1) covalently modifying one of the click chemistry reaction groups to a hydrophilic polymer, wherein the click chemistry reaction groups on the hydrophilic polymers of different molecular weights are the same and dissolved in an aqueous solution; 2) covalently modifying the other group of the click chemistry reaction group pair onto a block polymer, and the click chemistry reaction groups on different types of block polymers are the same and dissolved in an aqueous solution; 3) The solution obtained in step 1) and the solution obtained in step 2) are mixed evenly according to a click chemistry reaction group molar ratio of 0.1 to 10, and after applying the mixed solution to the surface of the tissue to be bonded, wait for 10 seconds to 500 minutes to allow the click chemistry reaction in the polymer to fully proceed, so as to achieve stable adhesion with the tissue.
6. The method of use according to claim 5, characterized in that: The concentration of the polymer aqueous solution described in step (1) is 10-60% (w / v), preferably 20-50% (w / v); the photoinitiator described in step (2) includes lithium phenyl-2,4,6-trimethylbenzoyl phosphinate, and the light-induced wavelength range is 200-700nm; the chemical initiator includes ammonium persulfate / tetramethylethylenediamine; the concentration of the polymer mixed solution described in step 3) is 10-60% (w / v), preferably 20-50% (w / v).
7. The method of use according to claim 5, characterized in that: The aqueous solution is a solution containing bioactive substances or biocompatible substances, and the bioactive substances are exosomes, vitamins, amino acids, mineral elements, microecological regulators, platelet-rich plasma (PRP), platelet-rich plasma fibrin (PRF), growth factors or blood. Biocompatible substances include starch, cellulose, chitosan, sodium alginate, hyaluronic acid, pullulan, xanthan gum, collagen, gelatin, fibrin and their derivatives, which refer to pure water or aqueous solutions containing biocompatible substances that do not affect the polymerization of the adhesive into a gel.
8. Use of the high-strength, low-swelling injectable tissue adhesive according to any one of claims 1 to 4 as a wound sealing dressing.
9. Use of the high-strength, low-swelling injectable tissue adhesive according to any one of claims 1 to 4 as a postoperative anti-adhesion agent.
10. Use of the high-strength, low-swelling injectable tissue adhesive according to any one of claims 1 to 4 as a coating product for implantable devices.